Investigation of SLC2A1 26177A/G gene polymorphism via high resolution melting curve analysis in Malaysian patients with diabetic retinopathy - Ng, Z.X.; Kuppusamy, U.R.; Tajunisah, I.; Fong, K.C.S.; Chua, K.H. (2012)
Purpose In this study, we aimed to investigate the possible association between SLC2A126177A/Gpolymorphism and diabetic retinopathy (DR) in Malaysianpatients with type 2 diabetes. Methods Genomic DNA was extracted from 211 Malaysian type 2 diabeticpatients (100 without retinopathy DNR, 111 with retinopathy) and 165 healthy controls. A highresolutionmelting assay developed in this study was used to detect SLC2A126177A/Gpolymorphism followed by statistical analysis. Results A statistically significant difference in 26177 G minor allele frequency between healthy controls (19.7 %) and total patient group (26.1 %) (p < 0.05, Odd ratio = 1.437, 95% Confidence interval = 1.015â2.035) as well as between healthy controls (19.7 %) and DNR patients (27.5%) (p < 0.05, Odd ratio = 1.546, 95% Confidence interval = 1.024â2.336) was shown in this study. However, when compared between DR and DNR patients, there was no significant difference (p > 0.05). Conclusions This is the first study which shows that SLC2A1 26177G allele is associated with type 2 diabetes in Malaysian population but not with DR.